(K)ó(r)gjörningur? Hugleiðing um óhefðbundnar leiðir til að nálgast hljóðfærið kór á skapandi hátt og höfða til nýrra áhorfenda - Maríus Hermann Sverrisson 1973- (2014)
This report describes my work during my time as a student at the NAIP programme at the Iceland University of the Arts 2012–2014. In the Introduction I explain my initial intentions with joining the programme. In the second chapter, on the NAIP programme itself, I recounted and reflected upon my leading and guiding experiences during my studies, for instance, my work with the Swedish art group MEDIS 5, and several workshops in Iceland. Furthermore, I introduced my basic research topic, choir as a happening. In the third and most important chapter I go into detail about my work with the women‘s choir, Hrynjandi, and our quest for new audiences through innovative practice. The fourth chapter describes my graduation concert, where I performed both as a soloist and as a part of a larger ensemble, concluding with a performance by my choir, where I performed as a conductor. The last chapter´s reflect and summon up my time as a NAIP student and my work with Hryndjandi and conclude the report, with reflections on man‘s need to connect to each other through art.